Intertidal gastropod diversity in hard-bottom habitats as an indicator of habitat quality along Tomini Bay Coastline, Gorontalo, Indonesia - MIFTAHUL KHAIR KADIM; NURALIM PASISINGI; FAIZAL KASIM; SANDRIANTO DJUNAIDI; SUCIYONO SUCIYONO; YENNY RISJANI; MUHAMAD ROEM (Society for Indonesian Biodiversity, 2026)
Abstract. Kadim MK, Pasisingi N, Kasim F, Djunaidi S, Suciyono, Risjani Y, Roem M. 2026. Intertidal gastropod diversity in hard-bottom habitats as an indicator of habitat quality along Tomini Bay Coastline, Gorontalo, Indonesia. Biodiversitas 27 (2): d270207. https://doi.org/10.13057/biodiv/d270207. Gastropods are reliable bioindicators for evaluating environmental quality. Therefore, understanding their species diversity, especially in hard-bottom habitats is essential for ecological assessment and coastal management. This study aimed to explore the spatial diversity of gastropods inhabiting hard-bottom substrates along the Tomini Bay Coastline in Gorontalo, Indonesia and assess their potential as indicators of coastal water quality. Surveys were conducted at five main stations comprising 21 sub-stations and community structure was analyzed using diversity indices and biotic metrics. A total of 195 species representing 33 families were recorded, with Muricidae, Conidae, and Neritidae as dominant families. Planaxis sulcatus together with Nerita senegalensis and Littoraria scabra contributed substantially to overall abundance. Gastropod diversity exhibited marked spatial variation in community structure among stations. This variation was primarily influenced by turbidity, dissolved oxygen and orthophosphate concentration, which were identified as the key drivers differentiating environmental conditions across sites. Habitat quality assessment indicated slightly polluted conditions but overall maintained good ecological status. These findings demonstrate the sensitivity of intertidal gastropod assemblages to environmental gradients and reinforce their value as effective bioindicators for long-term biodiversity monitoring and coastal ecosystems management in tropical hard-bottom environments.